High-strength composite fabric and preparation method thereof

By interweaving aramid fiber and carbon fiber into a base layer, and calendering a PVB film layer on it, the problem of insufficient strength of existing composite fabrics is solved, and high strength, durability and protective performance are improved.

CN119329147APending Publication Date: 2025-01-21YONGSHENG HAEIL DIFFERENTIAL FABRIC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411462856.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-19
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The strength of existing composite bag fabrics is poor, resulting in a shorter service life in outdoor products.

Method used

The use of aramid fiber and carbon fiber is used as raw materials, which forms a basic layer through communication and extend the PVB membrane layer on the basic layer to form high -strength composite fabrics.

Benefits of technology

It improves the strength, falling, anti -cutting, thorns, and bulletproofing performance of composite fabrics, extend the service life, and is suitable for outdoor products such as bags and tents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005092380590000071
    Figure BDA0005092380590000071
  • Figure BDA0005092380590000081
    Figure BDA0005092380590000081
Patent Text Reader

Abstract

The invention discloses a high-strength composite fabric and a preparation method thereof, and belongs to the technical field of composite fabrics, the key points of the technical scheme are that the composite fabric comprises a base layer formed by interweaving aramid fibers and carbon fibers as raw materials, and a PVB film layer calendered on the base layer, the effect of improving the strength of the fabric for outdoor products such as bags and suitcases is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite fabrics, and in particular to a high-strength composite fabric and a preparation method thereof. Background Art

[0002] Luggage and bags are essential equipment in daily life, used to store daily clothes, etc. With the development of the times, the fabrics used to make luggage and bags have evolved from traditional genuine leather to polyester, polyamide, PU, ​​PVC and other materials.

[0003] The composite luggage fabric in the prior art generally includes a base layer and a first composite layer. The material of the base layer can be any one of flannel, non-woven fabric or cotton cloth. The first composite layer is glued to the base layer. Specifically, the first composite layer and the base layer are bonded by hot-melt adhesive. The resulting composite fabric has certain strength and service life and is relatively durable. However, since the base layer of the composite fabric is made of flannel, non-woven fabric or cotton cloth, its strength is relatively poor, resulting in a short service life of the composite fabric when used in outdoor products such as luggage. Summary of the invention

[0004] In order to improve the strength of fabrics for outdoor products such as bags, the present invention provides a high-strength composite fabric and a preparation method thereof.

[0005] The first object of the present invention is to provide a high-strength composite fabric, which adopts the following technical solution: A high-strength composite fabric comprises a base layer formed by interweaving aramid fibers and carbon fibers as raw materials, and a PVB film layer calendered on the base layer.

[0006] Preferably, the weight ratio of the aramid fiber to the carbon fiber is 1:(0.4-0.8).

[0007] Preferably, the aramid fiber is an aramid fiber that has been treated with plasma, and the conditions of the plasma treatment are: a vacuum degree of 10-40 Pa and a power of 200-600 W for 10-20 min.

[0008] Preferably, the base layer is immersed in the thickening liquid for 1-3 minutes and then pressed to remove excess thickening liquid, and then the immersed base layer is dried for use. The thickening liquid raw materials include 20-26 parts of styrene, 14-18 parts of acrylic acid, 0.05-0.08 parts of initiator, 0.3-0.4 parts of cross-linking agent, and 90-150 parts of ethylene glycol by weight.

[0009] Preferably, the thickening liquid is obtained by the following preparation method: S1: adding parts by weight of styrene, acrylic acid and water into a container, passing nitrogen, stirring at room temperature for 25-30 minutes, then adding an initiator and a cross-linking agent, stirring for 10 minutes, reacting in a water bath at 70-80° C. for 5-6 hours, collecting the reactants by centrifugation, washing the particles obtained after centrifugation and drying; S2: Add the particles obtained in step S1 into ethylene glycol and disperse them by ball milling for 20-24 hours to obtain a thickened solution.

[0010] Preferably, the cross-linking agent is divinylbenzene and the initiator is potassium persulfate.

[0011] Preferably, the PVB film layer raw material includes 100 parts of PVB resin and 15-30 parts of toughening agent by weight.

[0012] Preferably, the toughening agent is dioctyl terephthalate.

[0013] Preferably, the PVB resin has a hydroxyl content of 18-20%, a viscosity of 6.0-9.0 cps, and a Mw molecular weight of 40,000-70,000.

[0014] The second object of the present invention is to provide a method for preparing the high-strength composite fabric, comprising the following steps: S1, weaving aramid fiber and carbon fiber into a base layer; S2, calendered PVB film; S3, calendering the base layer and the PVB film to obtain a composite fabric.

[0015] In summary, the present invention has the following beneficial effects: 1. The composite fabric obtained by combining aramid fiber, carbon fiber and PVB film layer in this application has high strength, drop resistance, cut resistance, puncture resistance and bulletproof properties, and can be better used in outdoor products such as bags and tents, and can also be used in protective fabrics.

[0016] 2. After the aramid fiber is treated with plasma, the free radicals on the surface of the aramid fiber can be cracked, oxidized, transferred, etc., thereby generating active groups, improving the wettability of the aramid fiber surface, and enhancing the bonding strength between the aramid fiber and the thickening liquid. It effectively ensures that the particles in the thickening liquid are attached to the base layer, and reduces the amount of particles that fall off during later use. In this application, when the plasma treatment time is selected to be 10-20 minutes, the etching effect of the active ions on the aramid fiber can be effectively guaranteed, and the aramid fiber body will not be damaged. However, when the treatment time exceeds 20 minutes, the effect of the plasma gradually becomes significant, resulting in traces of peeling on the surface of the fiber, the fiber is damaged, and the strength of the fabric as well as the puncture and ballistic resistance are reduced.

[0017] 3. After the base layer woven from aramid fiber and carbon fiber is treated with thickening liquid, the puncture and ballistic resistance of the composite fabric can be effectively improved. The reason is that after the fiber is impregnated with the thickening liquid, the thickening liquid is evenly coated on the fiber surface, filling the gaps between the fibers, increasing the friction and cohesion between the fibers, and limiting the movement of the fibers during fiber extraction, thereby effectively improving the strength of the composite fabric.

[0018] 4. When the hydroxyl content in the PVB resin in the present application is selected to be 18-20% and the Mw molecular weight is 40000-70000, the bonding strength between the PVB film layer and the base layer can be effectively improved, ensuring that the high-strength composite fabric obtained in the present application has good flexibility. DETAILED DESCRIPTION

[0019] The present invention is further described in detail below with reference to the embodiments.

[0020] The raw materials used in the examples and comparative examples of the present application are all commercially available.

[0021] Example 1 A method for preparing a high-strength composite fabric comprises the following steps: S1, weaving aramid fiber and carbon fiber into a base layer in a weight ratio of 1:0.4; S2, calendering PVB film, specifically, mixing 10kg of PVB resin and 1.5kg of dioctyl terephthalate, a toughening agent, at 160°C for 10min, and then feeding the mixed material into a calender to calender the PVB film, the calendering temperature being 150°C, wherein the PVB resin is purchased from Kramar, and the specific properties are hydroxyl content of 18-20%, viscosity of 6.0-9.0cps, and Mw molecular weight of 40000-70000; S3. Send the base layer and the PVB film into a calender for lamination to obtain a composite fabric, and the calendering temperature is 120°C.

[0022] Example 2 A method for preparing a high-strength composite fabric comprises the following steps: S1, weaving aramid fiber and carbon fiber into a base layer in a weight ratio of 1:0.6; S2, calendering PVB film, specifically, mixing 10kg of PVB resin and 1.5kg of dioctyl terephthalate, a toughening agent, at 160°C for 10min, and then feeding the mixed material into a calender to calender the PVB film, the calendering temperature being 150°C, wherein the PVB resin is purchased from Kramar, and the specific properties are hydroxyl content of 18-20%, viscosity of 6.0-9.0cps, and Mw molecular weight of 40000-70000; S3. Send the base layer and the PVB film into a calender for lamination to obtain a composite fabric, and the calendering temperature is 120°C.

[0023] Example 3 A method for preparing a high-strength composite fabric comprises the following steps: S1, weaving aramid fiber and carbon fiber into a base layer in a weight ratio of 1:0.8; S2, calendering PVB film, specifically, mixing 10kg of PVB resin and 1.5kg of dioctyl terephthalate, a toughening agent, at 160°C for 10min, and then feeding the mixed material into a calender to calender the PVB film, the calendering temperature being 150°C, wherein the PVB resin is purchased from Kramar, and the specific properties are hydroxyl content of 18-20%, viscosity of 6.0-9.0cps, and Mw molecular weight of 40000-70000; S3. Send the base layer and the PVB film into a calender for lamination to obtain a composite fabric, and the calendering temperature is 120°C.

[0024] Example 4 A method for preparing a high-strength composite fabric comprises the following steps: S1, weaving aramid fiber and carbon fiber into a base layer in a weight ratio of 1:0.6; S2, calendering PVB film, specifically, 10kg of PVB resin and 2.4kg of dioctyl terephthalate, a toughening agent, are mixed and stirred at 160°C for 10 minutes, and then the mixed material is sent to a calender to calender the PVB film, and the calendering temperature is 150°C, wherein the PVB resin is purchased from Kramar, and the specific properties are hydroxyl content of 18-20%, viscosity of 6.0-9.0cps, and Mw molecular weight of 40000-70000; S3. Send the base layer and the PVB film into a calender for lamination to obtain a composite fabric, and the calendering temperature is 120°C.

[0025] Comparative Example 4 A method for preparing a high-strength composite fabric comprises the following steps: S1, weaving aramid fiber and carbon fiber into a base layer in a weight ratio of 1:0.6; S2, calendering PVB film, specifically, 10kg of PVB resin and 2.4kg of dioctyl terephthalate, a toughening agent, are mixed and stirred at 160°C for 10 minutes, and then the mixed material is sent to a calender to calender the PVB film, and the calendering temperature is 150°C, wherein the PVB resin is purchased from Kramar, and the specific properties are hydroxyl content of 11-13%, viscosity of 18-28cps, and Mw molecular weight of 90000-120000; S3. Send the base layer and the PVB film into a calender for lamination to obtain a composite fabric, and the calendering temperature is 120°C.

[0026] Example 5 A method for preparing a high-strength composite fabric comprises the following steps: S1, weaving aramid fiber and carbon fiber into a base layer in a weight ratio of 1:0.6; S2, calendering PVB film, specifically, 10kg of PVB resin and 3.0kg of dioctyl terephthalate, a toughening agent, are mixed and stirred at 160°C for 10 minutes, and then the mixed material is sent to a calender to calender the PVB film, and the calendering temperature is 150°C, wherein the PVB resin is purchased from Kramar, and the specific properties are hydroxyl content of 18-20%, viscosity of 6.0-9.0cps, and Mw molecular weight of 40000-70000; S3. Send the base layer and the PVB film into a calender for lamination to obtain a composite fabric, and the calendering temperature is 120°C.

[0027] Example 6 A method for preparing a high-strength composite fabric comprises the following steps: S1. Aramid fiber pretreatment: adjust the parameters of the remote microwave plasma device, adjust the power to 200W, put the aramid fiber in it, evacuate to a vacuum degree of 10Pa, and then introduce oxygen. After treating for 20 minutes, the plasma-treated aramid fiber is obtained. S2, taking the aramid fiber and the carbon fiber obtained in step S1 and weaving them into a base layer in a weight ratio of 1:0.6; S3, calendering PVB film, specifically, mixing 10kg of PVB resin and 2.4kg of dioctyl terephthalate, a toughening agent, at 160°C for 10 minutes, and then feeding the mixed material into a calender to calender the PVB film at a calendering temperature of 150°C, wherein the PVB resin is purchased from Kramar, and has specific properties of hydroxyl content of 18-20%, viscosity of 6.0-9.0cps, and Mw molecular weight of 40000-70000; S4. Send the base layer and the PVB film into a calender for lamination to obtain a composite fabric, and the calendering temperature is 120°C.

[0028] Example 7 A method for preparing a high-strength composite fabric comprises the following steps: S1. Aramid fiber pretreatment: adjust the parameters of the remote microwave plasma device, adjust the power to 600W, put the aramid fiber in it, evacuate to a vacuum degree of 40Pa, and then introduce oxygen. After treating for 20 minutes, the plasma-treated aramid fiber is obtained. S2, taking the aramid fiber and the carbon fiber obtained in step S1 and weaving them into a base layer in a weight ratio of 1:0.6; S3, calendering PVB film, specifically, mixing 10kg of PVB resin and 2.4kg of dioctyl terephthalate, a toughening agent, at 160°C for 10 minutes, and then feeding the mixed material into a calender to calender the PVB film at a calendering temperature of 150°C, wherein the PVB resin is purchased from Kramar, and has specific properties of hydroxyl content of 18-20%, viscosity of 6.0-9.0cps, and Mw molecular weight of 40000-70000; S4. Send the base layer and the PVB film into a calender for lamination to obtain a composite fabric, and the calendering temperature is 120°C.

[0029] Example 8 A method for preparing a high-strength composite fabric comprises the following steps: S1. Aramid fiber pretreatment: adjust the parameters of the remote microwave plasma device, adjust the power to 600W, put the aramid fiber in it, evacuate to a vacuum degree of 40Pa, and then introduce oxygen. After treating for 20 minutes, the plasma-treated aramid fiber is obtained. S2, taking the aramid fiber and the carbon fiber obtained in step S1 and weaving them into a base layer in a weight ratio of 1:0.6; S3, immersing the base layer: immersing the base layer obtained in step S2 in the thickening liquid for 1 minute, and then pressing to remove the excess thickening liquid, and then drying the immersed base layer at 60° C. for standby use, wherein the preparation process of the thickening liquid is as follows: (1) 20 kg of styrene, 14 kg of acrylic acid and 60 kg of water were added to a container, nitrogen was passed through, and the mixture was stirred at room temperature for 25 min. Then, 0.05 kg of initiator potassium persulfate and 0.3 kg of cross-linking agent divinylbenzene were added and stirred for 10 min. The mixture was reacted in a water bath at 70° C. for 6 h. The reactants were collected by centrifugation, and the particles obtained after centrifugation were washed with water and then dried. (2) adding the particles obtained in step S1 into 90 kg of ethylene glycol, ball milling and dispersion for 20 h, and then ultrasonicating for 1 h to obtain a thickening solution; S3, calendering PVB film, specifically, mixing 10kg of PVB resin and 2.4kg of dioctyl terephthalate, a toughening agent, at 160°C for 10 minutes, and then feeding the mixed material into a calender to calender the PVB film at a calendering temperature of 150°C, wherein the PVB resin is purchased from Kramar, and has specific properties of hydroxyl content of 18-20%, viscosity of 6.0-9.0cps, and Mw molecular weight of 40000-70000; S4. Send the base layer and the PVB film into a calender for lamination to obtain a composite fabric, and the calendering temperature is 120°C.

[0030] Example 9 A method for preparing a high-strength composite fabric comprises the following steps: S1. Aramid fiber pretreatment: adjust the parameters of the remote microwave plasma device, adjust the power to 600W, put the aramid fiber in it, evacuate to a vacuum degree of 40Pa, and then introduce oxygen. After treating for 20 minutes, the plasma-treated aramid fiber is obtained. S2, taking the aramid fiber and the carbon fiber obtained in step S1 and weaving them into a base layer in a weight ratio of 1:0.6; S3, immersing the base layer: immersing the base layer obtained in step S2 in the thickening liquid for 3 minutes, then pressing to remove the excess thickening liquid, and then drying the immersed base layer at 60° C. for standby use, wherein the preparation process of the thickening liquid is as follows: (1) 24 kg of styrene, 16 kg of acrylic acid and 60 kg of water were added to a container, nitrogen was passed through, and the mixture was stirred at room temperature for 25 min. Then, 0.06 kg of initiator potassium persulfate and 0.3 kg of cross-linking agent divinylbenzene were added and stirred for 10 min. The mixture was reacted in a water bath at 75° C. for 6 h. The reactants were collected by centrifugation, and the particles obtained after centrifugation were washed with water and then dried. (2) adding the particles obtained in step S1 to 120 kg of ethylene glycol, ball milling and dispersion for 20 h, and then ultrasonicating for 1 h to obtain a thickening solution; S3, calendering PVB film, specifically, mixing 10kg of PVB resin and 2.4kg of dioctyl terephthalate, a toughening agent, at 160°C for 10 minutes, and then feeding the mixed material into a calender to calender the PVB film at a calendering temperature of 150°C, wherein the PVB resin is purchased from Kramar, and has specific properties of hydroxyl content of 18-20%, viscosity of 6.0-9.0cps, and Mw molecular weight of 40000-70000; S4. Send the base layer and the PVB film into a calender for lamination to obtain a composite fabric, and the calendering temperature is 120°C.

[0031] Example 10 A method for preparing a high-strength composite fabric comprises the following steps: S1. Aramid fiber pretreatment: adjust the parameters of the remote microwave plasma device, adjust the power to 600W, put the aramid fiber in it, evacuate to a vacuum degree of 40Pa, and then introduce oxygen. After treating for 20 minutes, the plasma-treated aramid fiber is obtained. S2, taking the aramid fiber and the carbon fiber obtained in step S1 and weaving them into a base layer in a weight ratio of 1:0.6; S3, immersing the base layer: immersing the base layer obtained in step S2 in the thickening liquid for 3 minutes, then pressing to remove the excess thickening liquid, and then drying the immersed base layer at 60° C. for standby use, wherein the preparation process of the thickening liquid is as follows: (1) 26 kg of styrene, 18 kg of acrylic acid and 60 kg of water were added to a container, nitrogen was passed through, and the mixture was stirred at room temperature for 30 min. Then, 0.08 kg of initiator potassium persulfate and 0.4 kg of cross-linking agent divinylbenzene were added and stirred for 10 min. The mixture was reacted in a water bath at 80° C. for 5 h. The reactants were collected by centrifugation, and the particles obtained after centrifugation were washed with water and then dried. (2) adding the particles obtained in step S1 into 150 kg of ethylene glycol, ball-milling and dispersing for 24 h, and then ultrasonicating for 1 h to obtain a thickening solution; S3, calendering PVB film, specifically, mixing 10kg of PVB resin and 2.4kg of dioctyl terephthalate, a toughening agent, at 160°C for 10 minutes, and then feeding the mixed material into a calender to calender the PVB film at a calendering temperature of 150°C, wherein the PVB resin is purchased from Kramar, and has specific properties of hydroxyl content of 18-20%, viscosity of 6.0-9.0cps, and Mw molecular weight of 40000-70000; S4. Send the base layer and the PVB film into a calender for lamination to obtain a composite fabric, and the calendering temperature is 120°C.

[0032] Comparative Example 9 A method for preparing a high-strength composite fabric, which is different from Example 10 in that the thickening liquid is obtained by the following preparation method: 24 kg of nano-silicon dioxide (particle size is about 50 nm) particles are dispersed in 50 kg of anhydrous ethanol for 30 minutes, 90 kg of PEG200 is added and ultrasonically dispersed for 2 hours, and then 16 kg of carbon nanotubes (length is 10-30 microns) are added and ultrasonic treatment is continued for 48 hours to obtain the thickening liquid, and the rest is the same as Example 10.

[0033] Performance Testing The high-strength composite fabrics obtained in the above embodiments and comparative embodiments were stacked to form 36 layers of test specimens for stab and ballistic performance tests, wherein the stab test was carried out in accordance with "GA68-2019 Police Stab-Proof Clothing", the ballistic test was carried out with reference to "GA141-2010 Police Bulletproof Vests", and the tear strength test method was carried out in accordance with GB / T3917 tongue-shaped tearing, specifically with a descending speed of 500 mm / min, an ascending speed of 500 mm / min, an initial length of 100 mm, an ambient temperature of 25°C, an ambient humidity of 65%, a predetermined elongation of 70 mm, a peak amplitude of 5 N, a warp tear of 68.1 N, and a weft tear of 53.8 N. The test results are shown in Table 1.

[0034] Table 1 Composite fabric performance test results From the table above we can see that: The high-strength composite fabric obtained in Examples 1-3 of the present application can effectively protect against the impact force of at least 30J of impact energy. When the bulletproof performance test is performed, the bullet cannot be completely penetrated. This shows that the high-strength composite fabric obtained in the present application not only has good stab resistance, but also can maintain excellent bulletproof performance, effectively improving the protection effect for staff. In addition, the composite fabric of the present application also has excellent tearing performance, and can be effectively used in fabrics such as bags and tents to improve the service life of bags, tents, etc.

[0035] Compared with Example 2, when the content of dioctyl terephthalate, a toughening agent, in the PVB film is changed, the composite fabric obtained in Example 4-5 can withstand a higher impact force than that in Example 2, and the maximum impact energy can reach 42J, and the number of bullet penetration layers is reduced compared with that in Example 2, and the bonding strength between the PVB film layer and the base layer is further increased. It can be seen that when the content of dioctyl terephthalate, a toughening agent, in the PVB is further increased, the bonding strength between the PVB film layer and the base layer can be effectively improved, and the stab and ballistic resistance of the composite fabric can also be improved.

[0036] Comparative Example 4 Compared with Example 4, when the hydroxyl content in the PVB resin is 11-13%, the viscosity is 18-28cps, and the Mw molecular weight is 90000-120000, the impact force that the composite fabric obtained in Comparative Example 4 can withstand is lower than that in Example 4, and the bonding strength is also reduced. The reason may be that when the hydroxyl content in the PVB resin is relatively high, the hydroxyl group can form hydrogen bonds between and within the polymer molecules, thereby increasing the intermolecular force, thereby increasing the bonding strength between the PVB film and the base layer. When the bonding strength is relatively high, the separation or breakage between the PVB film layer and the base layer in the composite fabric can be effectively reduced, thereby ensuring the overall protective effect of the composite fabric.

[0037] Compared with Example 4, when the aramid fiber is treated with plasma, the impact force that the composite fabrics obtained in Examples 6-7 can withstand is increased compared with that in Example 4, and the bonding strength of the composite fabrics obtained in Examples 5-7 is further improved compared with that in Example 4. It can be seen that after the aramid fiber is treated with plasma, the bonding force between the base layer and the PVB film layer can be enhanced, thereby further improving the stab-proof performance of the composite fabric.

[0038] Compared with Example 7, after the base layer is treated with the thickening liquid, the impact force that the composite fabric obtained in Examples 8-10 can withstand is further increased, and the number of penetration layers is further reduced, indicating that after the base layer is treated with the thickening liquid, the stab-proof and ballistic-proof properties of the composite fabric are further improved. The reason is that the thickening liquid can be coated on the fiber surface and fill the gaps between the fibers, thereby increasing the friction and cohesion between the fibers, and limiting the movement of the fibers during fiber extraction, thereby effectively improving the stab-proof and ballistic-proof properties of the composite fabric.

[0039] Comparative Example 9 Compared with Example 9, when the base layer is treated with a thickening liquid made of nano-silicon dioxide and carbon nanotubes, the stab resistance and ballistic resistance of the resulting composite fabric are reduced compared to those in Example 9. It can be seen that the thickening liquid used in the present application can effectively improve the stab resistance of the composite fabric, thereby increasing the service life of the composite fabric.

[0040] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength composite fabric, characterized in that: The composite fabric comprises a base layer formed by interweaving aramid fiber and carbon fiber as raw materials, and a PVB film layer calendered on the base layer.

2. A high-strength composite fabric according to claim 1, characterized in that: The weight ratio of the aramid fiber to the carbon fiber is 1:(0.4-0.8).

3. The high-strength composite fabric according to claim 1, characterized in that: The aramid fiber is an aramid fiber that has been treated with plasma. The conditions of the plasma treatment are: a vacuum degree of 10-40 Pa and a power of 200-600 W for 10-20 minutes.

4. The high-strength composite fabric according to claim 1, characterized in that: The base layer is immersed in the thickening liquid for 1-3 minutes and then pressed to remove excess thickening liquid, and then the immersed base layer is dried for use. The thickening liquid raw materials include 20-26 parts of styrene, 14-18 parts of acrylic acid, 0.05-0.08 parts of initiator, 0.3-0.4 parts of cross-linking agent, and 90-150 parts of ethylene glycol by weight.

5. The high-strength composite fabric according to claim 4, characterized in that: The thickening liquid is obtained by the following preparation method: S1: adding parts by weight of styrene, acrylic acid and water into a container, passing nitrogen, stirring at room temperature for 25-30 minutes, then adding an initiator and a cross-linking agent, stirring for 10 minutes, reacting in a water bath at 70-80° C. for 5-6 hours, collecting the reactants by centrifugation, washing the particles obtained after centrifugation and drying; S2: Add the particles obtained in step S1 into ethylene glycol and disperse them by ball milling for 20-24 hours to obtain a thickened solution.

6. The high-strength composite fabric according to claim 4, characterized in that: The cross-linking agent is divinylbenzene, and the initiator is potassium persulfate.

7. The high-strength composite fabric according to claim 1, characterized in that: The PVB film layer raw material includes 100 parts of PVB resin and 15-30 parts of toughening agent by weight.

8. The high-strength composite fabric according to claim 7, characterized in that: The toughening agent is dioctyl terephthalate.

9. The high-strength composite fabric according to claim 7, characterized in that: The PVB resin has a hydroxyl content of 18-20%, a viscosity of 6.0-9.0 cps, and a Mw molecular weight of 40,000-70,000.

10. A method for preparing the high-strength composite fabric according to any one of claims 1 to 9, characterized in that: The steps include: S1, weaving aramid fiber and carbon fiber into a base layer; S2, calendered PVB film; S3, calendering the base layer and the PVB film to obtain a composite fabric.

Citation Information

Patent Citations

  • High strength fiber composite material, manufacturing method thereof and helmet using the same

    CN105264140A

  • Novel stab-resistant bulletproof composite fabric

    CN114055860A